(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Same sex behaviour is a piece of the considerable decent variety of human sexuality. MSM constitute a high risk group for sexually transmitted contaminations including HIV in numerous parts of the world and they stay at disproportionate risk for HIV infection and transmission. Since STD can encourage HIV transmission, an increase in STD among MSM might be related with an increment in HIV occurrence. Syphilis occurrence among men who engage in sexual relations with men (MSM) has been on the increase universally amid the most recent years. It is in light of this that this study went for researching the self-reported prevalence of STI among MSM, while evaluating their knowledge of STI and treatment seeking behaviour.